Emofiltrazioni a Confronto: Pre-Postdiluizione versus Doppia Filtrazione - P.L. Botti; R. Tarchini; G. Ferrari; C. Baraldi; M. Baruffaldi; M. Goldoni; P. Mastruzzi (AboutScience Srl, 1996)
Abstract non disponibile